Asymmetrical Triangular Current Mode (Atcm) for Bidirectional High Step Ratio Modular Multilevel Dc-Dc Converter - Rojas-Lobos, F; Cerda-Jimenez, C (Institute of Electrical and Electronics Engineers Inc., 2020)
Direct current (Dc) networks have proven advantages in high voltage direct current (HVDC) transmission systems, and now they are expanding to medium- and low-voltage distribution networks. One of the major challenges is to develop reliable dc-dc voltage transformation achieving high efficiency and performance, especially at high voltage and high step ratio. New resonant modular multilevel topologies have arisen as an alternative, mainly because of advantages such as optional use of transformers, natural voltage balance, simple control, and soft-switching capability. However, this type of operation generates a high peak current, does not allow control of power flow in all power range, and has a limited range of voltage variation. This article proposes an asymmetrical triangular current mode applied to high step ratio modular multilevel dc-dc converters. The proposed modulation increases the efficiency and achieves bidirectional control of the power, soft-switching, and a natural balance of the voltage in the cell capacitors. The experimental results show the bidirectional operation and the capacitor voltage balance of the converter under different operating conditions with higher efficiency (97.72%) and lower peak current compared to previous reports of this topology using resonant operation. © 1986-2012 IEEE.